الاقتصاد الجزائري حتمية الانطلاقة الصحيحة نحو تحقيق التنويع الاقتصادي في ظل التحولات الاقتصادية الإقليمية والدولية - عمان ،أحمد (جامعة الوادي University of Eloued, 2024)
This study aimed to demonstrate the necessity of Algeria seeking to achieve sustainable economic take-off, by achieving leaps in various fields and sectors, in order to avoid complete facus on the hydrocarbons sectorin the Algerian export mix. Through it, we have made an inventory of the terms related to economic take-off and necessary conditions for achieving it, and then we have attempted to evaluate the performance of the Algerian economy by applying the H.H index to measure economic diversification during the period 2014-2022, this is a period that witnessed several crises, including the collapse of oil prices in 2014 and the Covid 19 crisis in 2019 and the erosion of the country's exchange rserves, the imperative was reached to expand investments outside the hydrocarbon sector, enhance non-oil exports, increase the trend towards exploiting renewable energies, and provide more support for the industrial, agricultural and service sectors.
he Algerian economy: The inevitability of the right start towards achieving economic diversification in light of the regional and international economic transformations -an analytical study during the period: 2014-2024
Keywords: إقلاع اقتصادي; تنويع اقتصادي; نمو اقتصادي; اقتصاد جزائري; Economic take-off; Economic diversification; Economic Growth; Algerian economy